Electrocatalytic material, preparation method and application of electrocatalytic material in electrooxidation of urea

By preparing the electrocatalytic material of S-NiOOH-Ni(OH)2 on foam nickel, the problems of high equipment investment costs and strict requirements in urea wastewater treatment are solved, and simple and low-cost large-scale production and effective treatment of urea wastewater are achieved.

CN119912030AActive Publication Date: 2025-05-02ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510139775.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-05-02
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

When treating urea wastewater, the equipment investment cost is high and the conditions are strictly required, making it difficult to popularize it in small and medium-sized enterprises.

Method used

Using a preparation method of an electrocatalytic material, the nickel foam is treated successively, reacted with nickel nitrate hexahydrate and potassium persulfate, and then soaked in a solution containing sodium hypochlorite to prepare an electrocatalytic material supported on the nickel foam.

Benefits of technology

This method is simple, the equipment and raw materials are easy to obtain and the price is low, suitable for large-scale production, stable material quality, and can be effectively used for the treatment of urea wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912030A_ABST
    Figure CN119912030A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of electro-catalytic materials, and provides an electro-catalytic material, a preparation method and application of the electro-catalytic material in electro-oxidation of urea, and the preparation method comprises the following steps: treating foamed nickel with nitric acid, ethanol and deionized water in sequence; dissolving nickel nitrate hexahydrate and potassium persulfate in deionized water, then adding the treated foamed nickel, heating for reaction, cooling to room temperature, washing and drying to obtain an intermediate product; and soaking the intermediate product in a solution containing sodium hypochlorite, collecting the product, washing and drying. The S-NiOOH-Ni (OH) 2 loaded on the foamed nickel is prepared from simple and easily available raw materials through a two-step reaction, the preparation method is simple and convenient, the required equipment and raw materials are rich in source, low in price, easy to obtain and easy to repeat, the cost is easy to control in industrial production, the preparation method is suitable for large-scale production, and the material quality is stable; the prepared foamed nickel loaded S-NiOOH-Ni (OH) 2 electro-catalytic material can be used for urea wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to an electrocatalytic material, a preparation method and application thereof in electro-oxidation of urea. Background Art

[0002] Urea, with the chemical formula of CO(NH2)2, is a colorless or white needle-shaped or rod-shaped crystal. Urea is the most widely used nitrogen fertilizer product with the highest nitrogen content on the market. Urea is also widely used in the fields of medicine, food, cosmetics, textiles, etc. It is also an important raw material for the manufacture of chemical products such as melamine, urea-formaldehyde resin, and explosives. Due to the large production and use of urea, a large amount of urea wastewater (wastewater containing urea) is inevitably generated. Urea wastewater contains a large amount of ammonia nitrogen. If it is directly discharged into the environment, it will inevitably cause environmental pollution. If it enters rivers and lakes, it will cause eutrophication of water bodies, produce odor, and even cause the death of a large number of fish.

[0003] At present, the main treatment methods for urea wastewater include: chemical catalytic hydrolysis, thermodynamic hydrolysis, urease hydrolysis, chemical oxidation and biological hydrolysis, among which thermodynamic hydrolysis is the most commonly used technology in practice, but it is carried out under high temperature and high pressure, with high requirements for conditions, large power demand and high energy consumption, which is difficult for general small and medium-sized enterprises to bear. The above-mentioned urea wastewater treatment methods have problems such as high equipment investment cost and high requirements for conditions in industrial applications. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing an electrocatalytic material, aiming to solve the problems raised in the above background technology.

[0005] The present invention is implemented in this way: a method for preparing an electrocatalytic material comprises the following steps:

[0006] The nickel foam was treated with nitric acid, ethanol and deionized water in sequence;

[0007] Dissolve nickel nitrate hexahydrate and potassium persulfate in deionized water, add the treated nickel foam, heat and react, cool to room temperature after the reaction, collect the product, wash with ethanol and deionized water, and dry to obtain the intermediate product nickel foam loaded Ni(OH)2@Ni(SO4) 0.3 (OH) 1.4 ;

[0008] The intermediate product is immersed in a solution containing sodium hypochlorite, the product is collected, washed with ethanol and deionized water, and then dried to obtain an S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0009] Preferably, in the step of treating the nickel foam with nitric acid, ethanol and deionized water in sequence, the treatment is ultrasonic treatment for 10-15 min, and the concentration of the nitric acid is 1-1.2 mol / L.

[0010] Preferably, in the step of dissolving nickel nitrate hexahydrate and potassium persulfate in deionized water, the mass volume ratio of the nickel nitrate hexahydrate, potassium persulfate and deionized water is g:g:mL 0.58-2.32:0.1-0.4:30-60.

[0011] Preferably, in the step of heating the reaction, the heating temperature is 140-160° C. and the heating time is 8-12 hours.

[0012] Preferably, the preparation method of the solution containing sodium hypochlorite is: dissolving sodium hydroxide in a sodium hypochlorite solution, the effective chlorine content of the sodium hypochlorite solution is 3-15%, and the weight volume ratio of the sodium hydroxide to the sodium hypochlorite solution is g:mL 0.8-3.2:10-40.

[0013] Preferably, in the step of soaking the intermediate product in a solution containing sodium hypochlorite, the soaking time is 1-4 h and the temperature is 30-35°C.

[0014] Another object of an embodiment of the present invention is to provide an S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, which is prepared by the above-mentioned preparation method.

[0015] Another object of an embodiment of the present invention is to provide an application of S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam in electro-oxidation of urea.

[0016] Preferably, the electro-oxidation of urea is carried out in an H-type cell, the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on the nickel foam is used as the working electrode, the platinum sheet is used as the counter electrode, the reference electrode is a mercury-mercury oxide electrode, the anolyte is potassium hydroxide and urea, the catholyte is potassium hydroxide, and the urea is driven to undergo an electro-oxidation reaction when power is turned on.

[0017] Preferably, the potential applied during the power-on is 1.1-1.7 V compared to a standard hydrogen electrode.

[0018] A method for preparing an electrocatalytic material provided in an embodiment of the present invention adopts simple and easily available raw materials to prepare S-NiOOH-Ni(OH)2 loaded on nickel foam through a two-step reaction. The preparation method is simple, and the required equipment and raw materials are abundant and inexpensive, easy to obtain and repeat, easy to control costs in industrial production, suitable for large-scale production, and stable material quality; the prepared S-NiOOH-Ni(OH)2 loaded on nickel foam electrocatalytic material can be used for urea wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A transmission electron microscope image of the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam provided in Example 1 of the present invention;

[0020] Figure 2 The near-side X-ray absorption fine structure spectra of the sulfur element in the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam provided in Example 1 of the present invention and different comparative samples;

[0021] Figure 3 K-edge normalized absorption spectra of the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam and different comparative samples provided in Example 1 of the present invention;

[0022] Figure 4 This is a comparison diagram of linear sweep voltammetry curves of the samples prepared in Example 1 of the present invention and Comparative Example 1 in a mixed electrolyte of potassium hydroxide and urea;

[0023] Figure 5 The current variation curve of the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on the nickel foam provided in Example 1 of the present invention over time;

[0024] Figure 6 A curve showing the change of urea raw material concentration over time in the urea oxidation process using the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam provided in Example 1 of the present invention;

[0025] Figure 7 In order to apply the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on the nickel foam provided in Example 1 of the present invention to the product NH4 in the urea oxidation process + The concentration variation curve over time. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which comprises the following steps:

[0028] S1. Cut the nickel foam NF into 3-10 cm 2 According to the specifications, the cut nickel foam was ultrasonicated in 1 mol / L nitric acid for 10 min, in ethanol for 10 min, and in deionized water for 10 min.

[0029] S2, in the step of dissolving nickel nitrate hexahydrate and potassium persulfate in deionized water, nickel nitrate hexahydrate (0.58-2.32 g), potassium persulfate (0.1-0.4 g) and water (30-60 mL) are taken, and the treated nickel foam is also added to the reaction kettle solution, and heated (150 ° C, 10 h). After the reaction is completed and cooled to room temperature, the product is collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product;

[0030] S3, reacting the intermediate product in a solution containing sodium hypochlorite (0.8-3.2 g of sodium hydroxide dissolved in 10-40 mL of sodium hypochlorite solution with an effective chlorine content of 6%) for 3 h (temperature 35 °C), washing with deionized water and drying to obtain the final product, i.e., S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam;

[0031] The S-NiOOH-Ni(OH)2 electrocatalyst material loaded on the nickel foam is applied in the electrocatalytic urea oxidation, which specifically includes the following steps: an H-type electrolytic cell is set as an electrochemical reaction cell, a three-electrode system is adopted, the S-NiOOH-Ni(OH)2 electrocatalyst loaded on the nickel foam is used as a working electrode, the reference electrode is a mercury-mercury oxide electrode, the counter electrode is a platinum sheet, the electrolyte is 1 mol / L potassium hydroxide solution and 0.33 mol / L urea solution, and the potential applied when power is turned on is 1.1-1.7 V compared to the standard hydrogen electrode.

[0032] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0033] Example 1: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0034] Cut the 6 cm 2The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (1.16 g) and potassium persulfate (0.2 g) were selected as raw materials and dissolved in deionized water (30 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 6%) at 35 °C for 3 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0035] Example 2: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0036] Cut the 10 cm 2 The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (2.32 g) and potassium persulfate (0.4 g) were selected as raw materials and dissolved in deionized water (60 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (3.2 g sodium hydroxide, 40 mL sodium hypochlorite solution with an effective chlorine content of 6%) at 35 °C for 3 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0037] Example 3: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0038] Cut the 6 cm 2 The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (1.16 g) and potassium persulfate (0.2 g) were selected as raw materials and dissolved in deionized water (30 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 3%) at 35 °C for 3 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0039] Example 4: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0040] Cut the 6 cm 2 The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (1.16 g) and potassium persulfate (0.2 g) were selected as raw materials and dissolved in deionized water (30 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 15%) at 35 °C for 3 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0041] Example 5: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0042] Cut the 6 cm 2 The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (1.16 g) and potassium persulfate (0.2 g) were selected as raw materials and dissolved in deionized water (30 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 6%) at 35 °C for 2 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0043] Example 6: A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0044] Cut the 6 cm 2The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (1.16 g) and potassium persulfate (0.2 g) were selected as raw materials and dissolved in deionized water (30 mL) to obtain a solution; the treated nickel foam was added to the solution and heated in a high-pressure reactor at 150 °C for 10 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 6%) at 35 °C for 4 h to obtain S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

[0045] Comparative Example 1: A Ni-OOH electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:

[0046] Cut the 6 cm 2 The rectangular nickel foam was treated with nitric acid, ethanol and deionized water in sequence; analytical grade nickel nitrate hexahydrate (0.44 g) and urea (0.12 g) were selected as raw materials and dissolved in deionized water (30 mL); the treated nickel foam was added to the solution and heated in a high-pressure reactor at 200 °C for 12 h; after the reaction was completed and cooled to room temperature, the product was collected, washed with ethanol and deionized water, and then dried to obtain an intermediate product; the intermediate product was reacted in a sodium hypochlorite solution (1.6 g sodium hydroxide, 20 mL sodium hypochlorite solution with an effective chlorine content of 6%) at 35 °C for 3 h to obtain the final product, NiOOH-Ni(OH)2 electrocatalyst material supported on nickel foam.

[0047] Performance Test:

[0048] The S-NiOOH-Ni(OH)2 electrocatalytic material loaded on the nickel foam prepared in Example 1 was tested and a transmission electron microscope image was obtained as shown in FIG. Figure 1 As shown, it is proved that the material is made of Ni(SO4) 0.3 (OH) 1.4 and NiOOH; the near-side X-ray absorption fine structure spectra of sulfur elements in different comparison samples are as follows Figure 2 As shown in the figure, S-NiOOH-Ni(OH)2 has a sulfur oxidation peak of +6, indicating that the sulfur element in the material exists in the form of sulfate. It is compared with the nickel hydroxide comparison sample and the nickel foil comparison sample to obtain the K-edge normalized absorption spectrum as shown in the figure. Figure 3 As shown, it is proved that the valence state of nickel in S-NiOOH-Ni(OH)2 exceeds +2;

[0049] The samples prepared in Example 1 and Comparative Example 1 were cut into appropriate specifications and used as electrocatalytic materials to test their electro-oxidation performance in urea solution. An H-type electrolytic cell was set as an electrochemical reaction cell, and a three-electrode system was used. The anode chamber and the cathode chamber were separated by an anion exchange membrane. The sample was used as a working electrode, a platinum sheet was used as a counter electrode, and a mercury / mercury oxide electrode was used as a reference electrode. The electrolyte was 1 mol / L potassium hydroxide and 0.33 mol / L urea solution. When tested by an electrochemical workstation, the potential applied when power was turned on was 1.1-1.7 V compared to the standard hydrogen electrode, and the following was obtained: Figure 4 The linear sweep voltammetry curve shown in Figure 4 It can be seen that the electrocatalytic material prepared in the embodiment of the present invention reaches 505 mA / cm 2 The current density is only 1.4 V (relative to the standard hydrogen electrode); the stability test of the sample prepared in Example 1 is carried out, and the current variation curve over time is obtained as shown in Figure 5 When the sample prepared in Example 1 was used as an electrocatalytic material to test its electro-oxidation performance in a urea solution, a curve of the change of the raw material concentration over time was obtained as shown in Figure 6 As shown, the product NH4 + The concentration variation curve over time is as follows Figure 7 shown.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an electrocatalytic material, characterized in that: The following steps are involved: The nickel foam was treated with nitric acid, ethanol and deionized water in sequence; Dissolve nickel nitrate hexahydrate and potassium persulfate in deionized water, add the treated nickel foam, heat and react, cool to room temperature after the reaction, collect the product, wash with ethanol and deionized water, and dry to obtain the intermediate product nickel foam loaded Ni(OH)2@Ni(SO4) 0.3 (OH) 1.4 ; The intermediate product is immersed in a solution containing sodium hypochlorite, the product is collected, washed with ethanol and deionized water, and then dried to obtain an S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam.

2. The method for preparing an electrocatalytic material according to claim 1, characterized in that: In the step of treating the nickel foam with nitric acid, ethanol and deionized water in sequence, the treatment is ultrasonic treatment for 10-15 min, and the concentration of the nitric acid is 1-1.2 mol / L.

3. The method for preparing an electrocatalytic material according to claim 1, characterized in that: In the step of dissolving nickel nitrate hexahydrate and potassium persulfate in deionized water, the mass volume ratio of the nickel nitrate hexahydrate, potassium persulfate and deionized water is g:g:mL 0.58-2.32:0.1-0.4:30-60.

4. The method for preparing an electrocatalytic material according to claim 1, characterized in that: In the step of heating the reaction, the heating temperature is 140-160° C. and the heating time is 8-12 hours.

5. The method for preparing an electrocatalytic material according to claim 1, characterized in that: The preparation method of the solution containing sodium hypochlorite is as follows: dissolving sodium hydroxide in a sodium hypochlorite solution, wherein the effective chlorine content of the sodium hypochlorite solution is 3-15%, and the weight-to-volume ratio of the sodium hydroxide to the sodium hypochlorite solution is 0.8-3.2 g:10-40.

6. The method for preparing an electrocatalytic material according to claim 1, characterized in that: The intermediate product is immersed in a solution containing sodium hypochlorite for 1-4 hours at a temperature of 30-35°C.

7. A S-NiOOH-Ni(OH)2 electrocatalytic material loaded on nickel foam, characterized in that: The preparation method is as described in any one of claims 1 to 6.

8. Use of the S-NiOOH-Ni(OH)2 electrocatalytic material supported on nickel foam as claimed in claim 7 in electro-oxidation of urea.

9. The use according to claim 8, characterized in that: The electro-oxidation of urea is carried out in an H-type cell, the S-NiOOH-Ni(OH)2 electrocatalytic material loaded on the nickel foam is used as the working electrode, the platinum sheet is used as the counter electrode, the mercury-mercury oxide electrode is selected as the reference electrode, the anolyte is potassium hydroxide and urea, the catholyte is potassium hydroxide, and the urea is driven to undergo an electro-oxidation reaction when power is turned on.

10. The use according to claim 9, characterized in that: The potential applied during the power-on is 1.1-1.7 V compared to a standard hydrogen electrode.

Citation Information

Patent Citations

  • Nickel alloy-organic framework electrocatalyst as well as preparation method and application thereof

    CN115679374A

  • Preparation method of self-supporting bifunctional electrolyzed water catalyst

    CN116876022A

  • Self-supporting electrode and preparation method and application thereof

    CN119108569A

  • Preparation method of noble metal doped ultrathin hydroxide nano-cluster type electro-catalytic material

    CN119372702A

  • Ni-MOF thin-film photocatalyst grown in-situ on foamed nickel surface, preparation method therefor, and use thereof

    WO2022041852A1